2006
DOI: 10.3200/jrlp.140.6.579-590
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Belief in Paranormal Phenomena: Gestalt/Feature-Intensive Processing Theory and Tendencies Toward ADHD, Depression, and Dissociation

Abstract: Belief in paranormal phenomena and cryptids--unknown animals such as Bigfoot--may predispose individuals to interpret real-world objects and events in the same way that eyewitness identification can be biased by unrelated information (P. James and N. Thorpe, 1999). Psychological tendencies toward attention deficit hyperactivity disorder (ADHD), dissociation, and depression, even at subclinical levels, may be associated systematically with particular paranormal or cryptozoological beliefs. The authors evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Witnesses who provide erroneous elements of backstory, of the future actions taken by a perpetrator, or even of personal involvement in the situation, need not be consciously lying; rather, they need only to have beliefs about what might have happened in the past, or about what might happen next, for those beliefs to become inextricably intertwined in the gestalt representations which may ultimately result in an erroneous conviction. The present results provide data on the relative prevalence with which these several types of error may occur; future research is absolutely essential to explore the sources of these errors, especially in terms of individual psychology (see Sharps et al 2006;Sharps et al 2007) and of the ramifications of these errors both for cognitive representations in the abstract and for the application of such representations in real-world police and courtroom proceedings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Witnesses who provide erroneous elements of backstory, of the future actions taken by a perpetrator, or even of personal involvement in the situation, need not be consciously lying; rather, they need only to have beliefs about what might have happened in the past, or about what might happen next, for those beliefs to become inextricably intertwined in the gestalt representations which may ultimately result in an erroneous conviction. The present results provide data on the relative prevalence with which these several types of error may occur; future research is absolutely essential to explore the sources of these errors, especially in terms of individual psychology (see Sharps et al 2006;Sharps et al 2007) and of the ramifications of these errors both for cognitive representations in the abstract and for the application of such representations in real-world police and courtroom proceedings.…”
Section: Discussionmentioning
confidence: 92%
“…We have no idea of the dynamics or personal experiences underlying these specific cases. However, the documentation of this type of very rare effect may help to explain situations in which respondents report personal involvement in fantastic episodes in the forensic realm, or even with reference to alleged supernatural encounters (e.g., Sharps et al 2006), without any indication, from polygraph or other sources, that they are lying.…”
Section: Discussionmentioning
confidence: 95%
“…These predictive associations were suggested by theoretical considerations discussed in detail in the previous article (Sharps et al 2006). For example, depressed individuals can relate to ghosts as evidence of an afterlife in which things might get better.…”
mentioning
confidence: 86%
“…In an earlier paper (Sharps et al 2006), we found that specific psychological tendencies were systematically associated with particular types of paranormal or cryptozoological beliefs. These tendencies, evaluated by means of standard psychological instruments, included subclinical levels of hyperactivity/impulsiveness, dissociation, and depression.…”
mentioning
confidence: 96%
See 1 more Smart Citation